Is Peroneus Longus autograft a safe and effective alternative for Anterior Cruciate Ligament Reconstruction? (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcomes Peroneus Longus (PL) autograft for Anterior Cruciate Ligament Reconstruction (ACLR).Methods: This descriptive study was conducted in AO Hospital Karachi Pakistan from 21st January 2020 to 21st January 2022. All adults patients with Anterior Cruciate Ligament (ACL) tear fulfilling the inclusion criteria were treated arthroscopically with ipsilatera PL autograft. Post operative knee function was assessed with International Knee Documentation committee (IKDC) score and Tegner-Lysholm score at three months, six months, one year and two years follow up. Ipsilateral Ankle and foot function was assessed with American Orthopaedic Foot and Ankle Society (AOFAS) score. Pain intensity was measured with Visual Analogue Scale (VAS).Results: We operated 30 patients of ACL tear with ipsilateral Peroneus Longus tendon autograft. The mean age was 27.73± 4.14 years. All patients were male. Left knee was operated in 18(60%) and right in 12(40%). At two years follow up the IKDC score and Tegner-Lysholm score significantly improved from pre operative 50.87±12.96 and 66.86±16.96 to 90.40±5.98 and 96.53±5.73 respectively (p